Resistance to Nucleoside Analog Reverse Transcriptase Inhibitors Mediated by Human Immunodeficiency Virus Type 1 p6 Protein - Peters, Solange (American Society for Microbiology, 2001)
Resistance of human immunodeficiency virus type 1 (HIV-1) to antiretroviral agents results from target gene mutation within the pol gene, which encodes the viral protease, reverse transcriptase (RT), and integrase. We speculated that mutations in genes other that the drug target could lead to drug resistance. For this purpose, the p1-p6(gag)-p6(pol) region of HIV-1, placed immediately upstream of pol, was analyzed. This region has the potential to alter Pol through frameshift regulation (p1), through improved packaging of viral enzymes (p6(Gag)), or by changes in activation of the viral protease (p6(Pol)). Duplication of the proline-rich p6(Gag) PTAP motif, necessary for late viral cycle activities, was identified in plasma virus from 47 of 222 (21.2%) patients treated with nucleoside analog RT inhibitor (NRTI) antiretroviral therapy but was identified very rarely from drug-naïve individuals. Molecular clones carrying a 3-amino-acid duplication, APPAPP (transframe duplication SPTSPT in p6(Pol)), displayed a delay in protein maturation; however, they packaged a 34% excess of RT and exhibited a marked competitive growth advantage in the presence of NRTIs. This phenotype is reminiscent of the inoculum effect described in bacteriology, where a larger input, or a greater infectivity of an organism with a wild-type antimicrobial target, leads to escape from drug pressure and a higher MIC in vitro. Though the mechanism by which the PTAP region participates in viral maturation is not known, duplication of this proline-rich motif could improve assembly and packaging at membrane locations, resulting in the observed phenotype of increased infectivity and drug resistance.